The Discourse of Spiritual Abuse in Claire Vaye Watkin's "Gold Fame Citrus" - Lailatut Tarwiyah; Tirmidi Tirmidi (Prosodi Jurnal Ilmu Bahasa dan Sastra, 2026)
This study examines the discourse of spiritual abuse in Claire Vaye Watkins' novel Gold Fame Citrus. It addresses the limitations of discussions of spiritual abuse in literary studies, particularly regarding the use of spiritual language and moral authority as tools of ideological control in dystopian narratives. The study aims to identify the root causes of spiritual abuse and analyze how spiritual language fosters obedience, authority, and psychological dependence. Using descriptive qualitative methods, this study applies discourse analysis and an intertextual approach to examine dialogues, narrative descriptions, and symbolic expressions in the text. The findings indicate that spiritual abuse is constructed through manipulative spiritual language, claims of moral authority, fear-based obedience, and psychological dependency. Moreover, in a dystopian society, spiritual discourse potentially served as, among other things, mean to legitimize domination and to maintain ideological power. Finally, the study concludes that language plays a crucial role in shaping belief systems and reinforcing symbolic violence through narrative discourse, thus contributing to discourse-based literary studies on spiritual abuse in contemporary dystopian fiction.